Peran Kegiatan OSIS Dalam Meningkatkan Kemampuan Public Speaking Siswa MAN 1 MUBA - Apri Juliansa; Eni Murdiati; Manalullaili Manalullaili (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
This study discusses "The Role of OSIS Activities in Improving Public Speaking Ability of MAN 1 Muba Students". The background of this research is due to the decrease in public speaking ability experienced by students of MAN 1 Muba which hinders students from presenting themselves in the school environment and outside of school. The purpose of this research is to find out the role of OSIS activities in improving the public speaking skills of MAN 1 MUBA students. The theory used in this research is Aristotle's Retrometric Theory and Da'wah Communication Accommodation Theory. This research is a descriptive research with a qualitative approach. Data collection techniques used in this study were documentation, interviews and observation techniques. Sources of research data were obtained through primary data obtained through observations and interviews conducted at MAN 1 MUBA, and secondary data obtained through websites, books, journals and other references related to the object of research, then analyzed using qualitative analysis techniques. The results of this study stated that the MAN 1 MUBA Student Council as a whole could carry out its role well through Public Speaking activities which had honed students' communication skills.